269. Clinical Characteristics and Outcomes of Persistent Staphylococcus aureus Bacteremia - Yang, Eunmi (Open Forum Infect Dis, 2020)
BACKGROUND: Staphylococcus aureus bacteremia (SAB) is a leading cause of bacteremia and persistent SAB is associated with poor outcomes. We evaluated key clinical characteristics and outcomes associated with persistent SAB. METHODS: We reviewed patients enrolled in a prospective cohort of adult patients with S. aureus bacteremia at a tertiary hospital from August 2008 to December 2018. Clinical characteristics, outcomes, and microbiologic characteristics of patients with persistent bacteremia (≥ 3 d) were evaluated. RESULTS: Of the total 969 patients, 617 (63.7%) patients had persistent bacteremia. The median duration of bacteremia with persistent bacteremia was 5 days. The most common sources of persistent bacteremia were central venous catheter-related infection (33.4%) and bone and joint infection (14.9%). Methicillin resistant S. aureus (MRSA) isolates were analyzed in 372 (60.3%) patients and metastatic infections were 217 (35.2%) with persistent bacteremia. In the multivariate analysis, APACHE Ⅱ score (adjusted odds ratio [aOR], 1.07; 95% confidence interval [CI], 1.03–1.10), Charlson comorbidity index score (aOR, 1.14; 95% CI, 1.04–1.25), liver cirrhosis (aOR, 2.47; 95% CI, 1.44–4.23), and S. aureus pneumonia (aOR, 3.04; 95% CI, 1.29–7.18) were independently associated with 30-d mortality. In persistent MRSA bacteremia, ST5-SCCmecⅡ was 59.7% (222/372) and agr dysfunction was 64.8% (241/372). After adjusting for confounding factors, APACHE Ⅱ score (aOR, 1.08; 95% confidence interval [CI], 1.04–1.12), liver cirrhosis (aOR, 3.09; 95% CI, 1.56–6.14), and S. aureus pneumonia (aOR, 4.37; 95% CI, 1.40–13.67) were independently associated with 30-d mortality. Table 1. Demographic and Clinical characteristics of Patients With Persistent Bacteremia [Image: see text] Table 2. Microbiologic Characteristics and Genotypes in MRSA Isolates Responsible for Persistent Bacteremia [Image: see text] Fig 1. Duration of Staphylococcus aureus bacteremia [Image: see text] CONCLUSION: In persistent bacteremia, clinical factors, including APACHE Ⅱ score, Charlson comorbidity index score, liver cirrhosis, and S. aureus pneumonia contribute to 30-d mortality. DISCLOSURES: All Authors: No reported disclosures